Technology parks, knowledge transfer and innovation: the case of Malaysia’s information and communication technology (ICT) small and medium enterprises - Mhd. Sarif, Suhaimi; Ismail, Yusof (Inderscience Publishers, 2006)
This paper attempts to explore the views of key ICT stakeholders on the role of technology parks in promoting innovation via knowledge transfer. Many developed and developing countries use technology parks as an instrument to promote knowledge transfer and innovation. Policy makers incorporate this idea into public policy for science and technology. The study observes that Malaysia’s technology parks have played a little role in promoting knowledge transfer and innovation because ICT enterprises located thereon operate on a different premise. The study suggests the government to review the policy on technology parks with the objective to intensify innovation in Malaysia’s ICT industry.